Comparative Analysis of Quality of Service (QOS) on 4G LTE and 5G Networks in Bekescsaba Hungary - Dery Adlil Karim; Sri Yusnita; Dikky Chandra (International Journal of Wireless And Multimedia Communications, 2025)
This research discusses the comparison of Quality of Service (QoS) performance on 4G LTE and 5G networks in the Bekescsaba region, Hungary. The analysis was conducted based on five main QoS parameters, namely download speed, upload speed, jitter, packet loss, and latency, with the RSRP (Reference Signal Received Power) measurement category. The results showed that 5G networks consistently outperformed 4G LTE in almost all categories. For example, in the Very Good category, 5G networks recorded download speeds of up to 196 Mbps, upload speeds of 91.5 Mbps, and latency of 25 ms, significantly better than 4G LTE. In the Good and Fair categories, the 5G network continued to show significant advantages in data speed and latency, although the jitter values were relatively comparable to 4G LTE. In addition, packet loss on both networks was recorded at 0%, indicating a high level of reliability. This study concludes that 5G networks provide a better experience in supporting modern connectivity needs than 4G LTE, even under less than optimal signal conditions. The findings are expected to serve as a reference for future telecommunications infrastructure development.